PENGARUH KUALITAS PRODUK DAN CITRA MEREK TERHADAP LOYALITAS KONSUMEN PASTA GIGI PEPSODENT PT. UNILEVER - Widiana, I Wayan Plong; Sukawati, Tjok. Gede Raka (E-Jurnal Manajemen, 2016)
This research was conducted in the city of Denpasar, the sample size used was 120 respondents using non-probability sampling technique particularly purposive sampling. The data collected were processed using multiple linear regression analysis technique. The results showed that tested each variable has valid and reliable, and have viable models according to the classical assumption that research can be done. Two independent variables (Quality Product and Brand Image) positive and significant impact on Consumer Loyalty Pepsodent toothpaste in Denpasar. Based on the research results suggested that the management to improve product quality Pepsodent toothpaste, because it will affect the Consumer Loyalty Pepsodent toothpaste. This study was conducted to assess consumer behavior towards loyalty to consume a product that is affected by product quality and brand image.
Keywords: Product Quality, Brand Image, Customer Loyalty